Eugenic appropriations of the goddess Isis: Reproduction and racial superiority in theosophical feminist writings - Albrecht, Jessica (Orbis Litterarum, 2023)
The goddess Isis continues to be an influential figure for the notion of the Divine Feminine in contemporary esoteric and popular thought. However, looking back into the history of modern esotericism, the image of the goddess Isis has been used by Theosophists such as Florence Farr and Frances Swiney to argue for their feminist and more importantly eugenic interpretations of the power of that goddess. This article examines the writings of these two Theosophists together to highlight the eugenics aspects of their vision of Isis as the perfect mother and the superwoman. Through this, Isis became a symbol for a specific gendered aspect of religious eugenics by changing the meaning of the Divine Feminine. This is one of the roots of contemporary Isis interpretations leading to a prevalent idea of fertility and the gendered divine.
Created from Fastlane, Scopus look-up
Keywords: eugenics; feminism; goddess; sexuality; superwoman; theosophy